Arthroscopy Revision of Medial Meniscus Posterior Root (MMPR) Reconstruction Using Gracillis Tendon Graft. A Case Report. Issue 2 (31st January 2023) - Setyawan, Wahyu; Artha, Arrisna
The techniques for medial meniscal posterior roots (MMPR) repair can vary in relationship to the surgical approach, type of suture, device used, and fixation technique. Anatomic reduction, meniscal root fixation, and prevent extursion are possible by the trans-tibial pull-out repair procedure for MMPR tears. But it has been found that it has a substantially weaker than the natural root with unsactisfactory healing rates. Objective: We purposed this technique to reduce the failure of meniscus repair with a more anatomical, better healing and reproducible outcome Case Presentation: A 60-year-old female patient with Medial Meniscus Posterior Root tear LaPrade classification type 2. She had arthroscopic transtibial pull-out meniscal root repair using Ethibond No. 5 non-absorbable suture material. Six months after surgery, she had retear on MMPR and we performed the arthroscopic MMPR reconstruction with gracilis tendon graft. 3 months after surgery, patient has a good function and MRI evaluation. Conclusion: This arthroscopic medial meniscus posterior root reconstruction using gracilis graft is provide an anatomical repair, a more strong with a biological healing than previous repair techniques.